Determination of total vicinal diketones in beer by headspace capillary gas chromatography: Submitted on behalf of the EBC Analysis Committee - Dupire, S. (BrewingScience, 1998)
The determination of total vicinal diketones in beer by tht headspace capillary gas chromatography method of the Institute of Brewing Analysis Committee has been collaboratively tested by the members of the Analysis Committee of the European Brewery Convention. Two collaborative trials on three beer samples were performed in 14 laboratories. Repeatability (r₉₅) and reproducibility (R₉₅) values were obtained for 9 laboratories over the range of 20 to 94 μg. It was judged that reproducibility coefficients ranging after the second test from 31 to 94 were poor but it was decided that the method should nevertheless be included in the Analytica EBC as a guideline method with notice on its poor precision.